2015
DOI: 10.4049/jimmunol.1402405
|View full text |Cite|
|
Sign up to set email alerts
|

Modeling the Specific CD4+ T Cell Response against a Tumor Neoantigen

Abstract: The antitumor activity of CD4+ T cells is increasingly acknowledged in both humans and mice. The involved mechanisms have been mostly studied using transplanted tumor mouse systems. In these models, many tumor cells die at the time of implantation leading to the release of Ag in an inflammatory context contrasting with the slow and nondestructive growth of early-stage human tumors. In this study, we show that the presentation of a MHC class II–restricted model Ag (male, DBY) released by dying tumor cells may l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…Thus, the bulk of tumour antigen in our model reached draining nodes in a DC-associated form, rather than as free antigen, suggesting that any 'accidental' release of tumour antigen was unlikely to have a major role in the induction of anti-tumour immunity. 33 A requirement for host APCs to prime naive tumour-reactive CD4 T cells has been reported even in those models in which direct MHCII-dependent interaction between tumour and CD4 T cells was demonstrated, 3 indicating that CD4 T-cell priming in cancer follows the same rules as priming to foreign antigen.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the bulk of tumour antigen in our model reached draining nodes in a DC-associated form, rather than as free antigen, suggesting that any 'accidental' release of tumour antigen was unlikely to have a major role in the induction of anti-tumour immunity. 33 A requirement for host APCs to prime naive tumour-reactive CD4 T cells has been reported even in those models in which direct MHCII-dependent interaction between tumour and CD4 T cells was demonstrated, 3 indicating that CD4 T-cell priming in cancer follows the same rules as priming to foreign antigen.…”
Section: Discussionmentioning
confidence: 99%
“…Most neoantigens of cancer cells can stimulate T cells and also induce a regulatory immune response [ 7 , 8 ]. Intratumoral CD4 + T cells are increasingly recognized as responsible for antitumor immune response and the production of inflammatory mediators that induce tumor growth, invasion, angiogenesis, and metastasis which are associated with clinical outcomes [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…By generating an MCA101-based tumor cell line with inducible expression of the MHC-II restricted model antigen DBY, Flament and colleagues demonstrated that antigen release from tumor cells results in efficient priming of tumor-specific, polyfunctional CD4 + T cells in the tumor draining lymph node capable of circulating to the tumor and secrete IFN-γ. 58 Notably, this tumor model will be very useful to gain a better understanding of how to efficiently generate antitumor CD4 + T cell responses for therapeutic purposes.…”
Section: Antibodies Helper T-cell Physiologymentioning
confidence: 99%